Kompetensi Guru Agama Islam dalam Membangun Suasana Belajar yang Efektif - Sukma Ayu Ningrum; Bahtiar Siregar; Ahmad Ridwan; Deva Nakia; Suriyadi Suriyadi; Ismalia Putriana Simbolon (Departement of Mathematics Education, 2024)
The competence of Islamic religion teachers in building an effective learning atmosphere is crucial for understanding the key role of teachers in religious education. The aim of this research is to determine the competence of teachers in creating an effective learning environment for students. This study is a literature review, based on the exploration of literature related to the issues to be discussed. Data in this literature review are obtained through searching and analyzing books, articles, magazines, journals, internet sources, and other relevant notes that support solving the problems in this research. Several factors can influence learning, including learning principles, teaching methods, and learning conditions. It is hoped that Islamic religion teachers can enhance their competence in creating an effective learning atmosphere by deepening their understanding of Islamic religious materials and improving communication skills.